An Unusual Presentation of Pelvic Leiomyomatosis Misdiagnosed as Disseminated Malignancy - Nisha Marwah; Amrita Duhan; Garima Aggarwal; Rajeev Sen (Case Reports in Pathology)
Leiomyomatosis peritonealis disseminata (LPD) is an exceedingly rare, usually benign condition that clinically simulates a disseminated malignancy, occurring predominantly in women of childbearing age. We present a case of LPD in a postmenopausal woman who had undergone hysterectomy 8 years back for fibroids along with simultaneous presence of pelvic metastasis from breast carcinoma.